Ratio Analysis of Social Media Platform Instagram Using The Exploratory Method - Saputra, I Wayan Kelvin Widana; Radhitya, Made Leo; Subawa, I Gede Arika (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
The notable surge in the adoption of Instagram as a promotional instrument by micro, small, and medium enterprises (MSMEs) underscores the criticality of evaluating the outcomes and efficacy of marketing approaches. This study underscores the criticality of Instagram social media ratios in facilitating effective consumer engagement and marketing strategies. Social media analysis employs an exploratory approach to identify variables on Instagram that will subsequently be transformed into ratios indicating whether or not they have a significant relationship. Utilizing variables including Post to Followers, Following to Followers, Image Likes to Followers, Image Comments to Followers, and Video Likes to Followers, the study's findings comprise a ratio analysis of the most active computer store Instagram account among the five accounts examined on Instagram.